THE RELATIONSHIP BETWEEN SECONDARY SCHOOL TEACHERS’ ORGANIZATIONAL SUPPORT PERCEPTIONS AND THEIR ORGANIZATIONAL CYNICISM ATTITUDES - Necmi GÖKYER; İsmail TÜRKOĞLU (International Journal of Eurasia Social Sciences, 2018)
This study aims to identify the relationship between secondary school teachers’ organizational support perceptions and their organizational cynicism attitudes. The population of this relational survey included 1,602 teachers who were working at the 55 secondary schools located in central Elazig during the 2016-2017 school year. A total of 389 teachers working at 13 randomly selected schools from among these were distributed the data collection tool. However, tools from only 319 teachers were ultimately analyzed. The results showed that secondary school teachers agreed with the organizational support and justice and organizational ownership sub dimensions and the entire scale, while they partially agreed with the personal and professional development sub dimension. The organizational support perceptions of teachers who did not consider leaving their schools were higher than those who were considering or partly considering leaving. Teachers’ organizational cynicism levels manifested at the highest level in the behavioral domain, followed by the cognitive and affective domains.